Environmental effects on the durability and the mechanical performance of flax fiber/bio-epoxy composites - Moudood, Abdul (2019)
The growing usage of bio-composite materials in different engineering applications demands a thorough understanding of their performance during their service. Extreme environmental conditions, such as warm, humid, and freezing environments, among others, can degrade the mechanical properties of the bio-composites when they are exposed to harsh environmental conditions. In addition, the use of these composites in underwater applications can also shorten their life cycle. In this work, the durability and mechanical performance (tensile and flexural behavior)of flax/bio-epoxy composites exposed to different environmental conditions were evaluated. These conditions were chosen to replicate those found outdoors that can affect the durability of these materials: water immersion, warm humid environment and freeze-thaw conditions. Moisture and water absorption behavior were evaluated and the water content (or exposure time)was related to the physical changes and mechanical properties. Results show that the mechanical properties of flax/bio-epoxy composites are clearly degraded by water ageing when they are compared to the ?as manufactured? composites. The tensile strength and modulus is decreased approximately by 9% and 57%, respectively for water saturated (immersed in water until saturation)samples compared to as manufactured samples. On contrary, this reduction rate is only 0.8% and 3%, respectively in case of humidity saturated (exposed to humid environment until saturation)samples. Furthermore, water incurred more severe effects on the flexural properties of the composites, since their flexural strength and modulus is decreased by 64% and 70%, respectively, as compared to as manufactured samples. It was found, however, that these properties can be partially regained after drying the water aged composites. Warm humid environments and freezing-thawing cycles have very little effect on the bio-composites.